Anastomotic leakage with abscess after laparoscopic sleeve gastrectomy for obesity: report of a series and review of literature. (June 2020) - Liu, Yang; Yang, Ning-Ning; Guan, Yong-Song; He, Qing
Anastomotic leakage with abscess is a rare but severe complication of bariatric surgery. However, there is currently a lack of attention regarding this complication. This study aimed to investigate the risk factors for this complication and relevant treatment strategies to call attention to this severe complication. We retrospectively reviewed the patients who were rehospitalized for anastomotic leakage with abscess after bariatric surgeries in West China Hospital of Sichuan University from November 2017 to November 2018. The clinical profiles analyzed included body mass index, body weight before and after surgery, postoperative hospital stay, diet prescriptions, treatment strategies, and outcomes. A total of six patients (two men and four women) were included. The mean baseline body mass index was 37.52 (29.84–43.37), and the mean weight was 104.95 kg (74.5–127.5). The chief complaints leading to rehospitalization were fever and dull abdominal pain. The average postoperative hospital stay was 3.3 (3–4) days, and the onset time ranged from 7 to 15 days. Finally, revision surgeries were performed in two of the six patients (33%), and they were all cured by percutaneous drainage-based treatments. The postoperative fever and abdominal pain were the signs of leakage and abscess. Similar patients should be followed up once a week for 3 weeks after bariatric surgery to facilitate the early recognition of this complication. A longer hospital stay and sufficient parenteral nutrition plus a later implementation of diet should be helpful to minimize this severe complication. Percutaneous drainage played a significant role in the treatment of these patients.